AN OVERVIEW OF EMPLOYEE DISCIPLINE OVERSIGHT IN THE NEWS SECTION OF PUBLIC BROADCASTING INSTATION RADION OF THE REPUBLIC OF INDONESIA - Imran Tahalua; Muhammad Arfah (Universitas Muhammadiyah Makassar, 2021)
The objective of the research were to asses the implementation of supervision and obstacles in the proses work discipline of empolyess at the news section of the Public Broadcasting Institation Radio Republic of Infonesia Makassar, as wal as supervision in the news section of LPP RRI. The research method employed was descriptive qualitative, which means that the research describes the findings of observations and direct interviews with employees. Final Project Writing is the result of research conducted in May 2021. After examing and the topic,the research finds that the work discipline in the work discipline has been going as evidencod by the high level of attendance and neatness thathas been maintance. The findings of this study should be to provied useful information to the institution.